Mucus cells in koi (Cyprinus carpio) scale epidermis. (7th March 2016) - DePasquale, Joseph A.
Abstract: Morphological and dynamic characteristics of epidermal mucus cells were examined in intact scales of Cyprinus carpio . Mucus cells were identified by alcian blue staining and live mucus cells characterized with differential interference contrast microscopy. Mucus cell pores were shown to be narrow slits or triangular‐shaped openings which are invariably situated at cell‐cell junctions. Small granules were often located at or just below the openings with larger granules positioned deeper into the cell. The large granules were observed to undergo a bubbling‐like activity, where a granule suddenly appears, enlarges and then abruptly disappears. Situated below the large granules is a dense matrix of quiescent small, tightly packed mucin granules. The findings suggest that mature epidermal mucus cells are structurally ordered with respect to secretory activity, where small numbers of initially basally located, densely packed granules rapidly expand in a location proximal to the pore and presumably prior to mucus release through the pore.